Wear-resistant nitrile composite material and preparation method thereof

By preparing modified flame retardants and antibacterial agents, and combining nano-silica and coupling agents, the flame retardant and antibacterial properties of nitrile butadiene composite materials were improved, solving the performance deficiencies of existing materials in high-temperature and high-humidity environments and meeting the demand for high-performance rubber additives.

CN120230334BActive Publication Date: 2025-11-04XINYA SAFETY TECH(HUAIAN) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510534539.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-11-04
Estimated Expiration
2045-04-27

AI Technical Summary

Technical Problem

Existing nitrile composite materials have shortcomings in terms of flame retardancy and antibacterial properties, especially in environments with high temperature, high humidity, or high risk of biological contamination, and cannot meet the high-performance requirements of modern industry.

Method used

By preparing modified flame retardants and modified antibacterial agents, specific chemical reactions are used to generate material components containing polyether bonds and hyperbranched structures. Combined with nano-silica and coupling agents, the flame retardant and antibacterial properties of the materials are improved.

Benefits of technology

It significantly improves the flame retardant and antibacterial properties of the material while maintaining good wear resistance and physical and mechanical properties, making it suitable for high-performance rubber additive manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a wear-resistant nitrile composite material and a preparation method thereof, and relates to the technical field of high polymer materials.The wear-resistant nitrile composite material comprises the following raw materials in parts by weight: 100 parts of nitrile rubber, 15-25 parts of nano-silicon dioxide, 8-12 parts of a plasticizer, 3-5 parts of zinc oxide, 1-3 parts of stearic acid, 2-3 parts of an antioxidant, 3-5 parts of a modified flame retardant, 5-8 parts of a modified antibacterial agent and 1-3 parts of a coupling agent.The 2-chloro-4-amino phenol is reacted with triethylene glycol monoethyl ether to generate a polyether bond compound; the polyether bond compound, paraformaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are reacted to generate a flame retardant compound; and hexachlorocyclotriphosphazene is reacted with the flame retardant compound to generate the modified flame retardant.The wear-resistant nitrile composite material prepared by the application has excellent flame retardant performance and antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer materials, in particular to a wear-resistant nitrile rubber composite material and a preparation method thereof. BACKGROUND

[0002] Nitrile rubber (NBR) is widely used in the fields of automobiles, aerospace, mechanical manufacturing, etc. due to its excellent oil resistance, wear resistance and aging resistance. However, with the rapid development of modern industrial technology, the requirements for material performance are increasingly improved, and the traditional nitrile rubber composite material has obvious shortcomings in terms of flame retardation and antibacterial performance. In some special application environments, such as high temperature, high humidity, flammable or high risk of biological pollution, the limitations of existing materials are increasingly prominent.

[0003] In terms of flame retardation, traditional nitrile rubber composite materials mostly rely on the addition of halogen-based flame retardants to meet the basic fireproofing requirements, but halogen-based flame retardants release a large amount of toxic and harmful gases when burning, which not only causes serious environmental pollution, but also poses a threat to human life safety. In addition, although some halogen-free flame retardants have improved environmental performance, they have poor dispersibility in the material, which easily leads to a decrease in physical properties such as tensile strength and tear strength, affecting the overall performance and service life of the material. In terms of antibacterial performance, existing nitrile rubber composite materials usually do not add effective antibacterial ingredients, or only add a small amount of antibacterial agents, which cannot meet the long-term and high-efficiency antibacterial requirements. In humid and high-risk biological pollution environments, microorganisms such as bacteria and mold are easily bred on the surface of the material, leading to material performance degradation such as surface corrosion, discoloration, and odor generation, which further affects the appearance and service life of the material, increases maintenance costs and replacement frequency.

[0004] Chinese invention patent with publication number CN103012881A discloses a high-temperature-resistant nitrile rubber composite material, which is composed of the following raw materials by weight: nitrile rubber 100 parts, zinc oxide 4-7 parts, stearic acid 1-2 parts, 4,4'-bis(α,α-dimethylbenzyl) diphenylamine 1.5-3 parts, silicate 40-120 parts, toning agent 0-40 parts, coupling agent 1-3.5 parts, polyester plasticizer 6-12 parts, and vulcanization accelerator 4-7 parts; the nitrile rubber composite material prepared by the invention has good high-temperature resistance, but the antibacterial and flame retardant properties are poor.

[0005] To solve the above problems, the present application provides a wear-resistant nitrile rubber composite material and a preparation method thereof, which aims to significantly improve the flame retardation and antibacterial performance of the material while maintaining good wear resistance and physical and mechanical properties, so as to meet the demand for high-performance rubber additives in modern industry. SUMMARY

[0006] In view of the shortcomings of the prior art, the present application aims to provide a wear-resistant nitrile rubber composite material and a preparation method thereof.

[0007] To achieve the above object, the present application is realized by the following technical solutions:

[0008] A wear-resistant nitrile composite material comprises the following raw materials in parts by weight:

[0009] 100 parts of nitrile rubber, 15-25 parts of nano-silicon dioxide, 8-12 parts of plasticizer, 3-5 parts of zinc oxide, 1-3 parts of stearic acid, 2-3 parts of antioxidant, 3-5 parts of modified flame retardant, 5-8 parts of modified antibacterial agent, and 1-3 parts of coupling agent;

[0010] The modified flame retardant is prepared by the following method:

[0011] S1: 2-chloro-4-amino phenol reacts with triethylene glycol monoethyl ether under the action of sodium hydroxide to generate a polyether bond compound;

[0012] S2: the polyether bond compound, paraformaldehyde, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are reacted to generate a flame retardant compound;

[0013] S3: under nitrogen protection, hexachlorocyclotriphosphazene is reacted with the flame retardant compound under the action of potassium carbonate to generate a modified flame retardant.

[0014] In step S1, the molar ratio of 2-chloro-4-amino phenol to triethylene glycol monoethyl ether is 1:(1.2-1.5).

[0015] In step S2, the molar ratio of paraformaldehyde, polyether bond compound, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is (2-3):1:(2-2.5).

[0016] In step S3, the molar ratio of hexachlorocyclotriphosphazene to the flame retardant compound is 1:(6-8).

[0017] The modified antibacterial agent is prepared by the following method:

[0018] S1: under nitrogen protection, 3-(bis(2-hydroxyethyl)amino)propionic acid methyl ester is reacted with 1,2-propanediol under the action of p-toluenesulfonic acid to generate a hyperbranched product;

[0019] S2: under nitrogen protection, 3-mercapto propionic acid is reacted with the hyperbranched product under the action of p-toluenesulfonic acid to generate a mercapto hyperbranched product;

[0020] S3: the mercapto hyperbranched product is continuously reacted with 3-mercapto propionic acid to generate a dithio hyperbranched product;

[0021] S4: under nitrogen protection, the dithio hyperbranched product is reacted with silver sulfadiazine under the catalysis of N,N'-dicyclohexyl carbodiimide to generate a modified antibacterial agent.

[0022] In step S1, the mass ratio of the methyl 3-(bis(2-hydroxyethyl)amino)propanoate to 1,2-propanediol is (25-30):5.

[0023] In step S2, the mass ratio of the 3-mercapto propanoic acid to the hyperbranched product is 6:(10-15).

[0024] In step S3, the mass ratio of the mercapto hyperbranched product to 3-mercapto propanoic acid is (18-20):6.

[0025] In step S4, the mass ratio of the dithio hyperbranched product to silver sulfadiazine is (15-20):4.

[0026] The plasticizer is one of dioctyl phthalate, diisononyl phthalate, dibutyl phthalate.

[0027] The antioxidant is one of antioxidant 1010, antioxidant 1076, antioxidant 168.

[0028] The coupling agent is one of gamma-aminopropyl triethoxysilane, vinyl triethoxysilane, gamma-methacryloyloxy propyl trimethoxysilane.

[0029] A preparation method of a wear-resistant nitrile composite material, comprising the following steps:

[0030] (1) weigh by weight parts: nitrile rubber 100 parts, nano silicon dioxide 15-25 parts, plasticizer 8-12 parts, zinc oxide 3-5 parts, stearic acid 1-3 parts, antioxidant 2-3 parts, modified flame retardant 3-5 parts, modified antibacterial agent 5-8 parts, coupling agent 1-3 parts;

[0031] (2) mix the nano silicon dioxide and the coupling agent in proportion, place in a high-speed stirrer and stir uniformly, the treatment time is 10-20 min, to obtain surface-modified nano silicon dioxide; mix the nitrile rubber, zinc oxide and stearic acid, pass through a banbury mixer at 120-150℃ for 5-10 min to make a masterbatch;

[0032] (3) add the masterbatch, surface-modified nano silicon dioxide, plasticizer, antioxidant, modified flame retardant, modified antibacterial agent into a double-screw extruder, set the temperature to 160-180℃, the screw rotation speed to 300-400 r / min, melt blend and then extrude and granulate; press the granulated composite material particles to form a wear-resistant nitrile composite material.

[0033] The application of a wear-resistant nitrile composite material in the field of additive manufacturing.

[0034] With the above technical solutions, the application has the following advantages:

[0035] (1) The present application generates a polyether bond compound by substitution reaction of the chlorine atom in 2-chloro-4-amino phenol and the hydroxyl group in triethylene glycol monoethyl ether; the polyether bond compound, paraformaldehyde, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide react to generate a flame retardant compound; the chlorine atom in hexachlorocyclotriphosphazene reacts with the hydroxyl group in the flame retardant compound to generate a hexa-substituted modified flame retardant.

[0036] (2) The modified flame retardant prepared by the present application contains multiple ether bonds in its structure, which can provide good flexibility and thermal stability; the flexibility and thermal stability of the ether bond help to form a continuous carbon layer during combustion, which can isolate oxygen and heat; at the same time, the flame retardant combines phosphorus and nitrogen, two flame-retardant elements, which can play a synergistic flame-retardant effect, effectively inhibit the combustion reaction, and reduce the generation of heat, thereby improving the flame-retardant performance of the material.

[0037] (3) The present application generates a hyperbranched product by the reaction of the ester group in 3-(bis(2-hydroxyethyl)amino) propionic acid methyl ester and the hydroxyl group in 1,2-propanediol; the carboxyl group in 3-mercaptopropionic acid reacts with the hydroxyl group in the hyperbranched product to generate a mercapto hyperbranched product; the mercapto group in the mercapto hyperbranched product continues to react with the mercapto group in 3-mercaptopropionic acid to generate a dithio hyperbranched product; the carboxyl group in the dithio hyperbranched product reacts with the amino group in silver sulfadiazine to generate a modified antibacterial agent.

[0038] (4) The hyperbranched structure in the modified antibacterial agent prepared by the present application provides more active sites and a larger specific surface area, enhancing the interaction between the antibacterial agent and the bacterial cell membrane; the dithio structure can react with the proteins and enzymes of bacteria, destroying the cell structure of bacteria; silver sulfadiazine has broad-spectrum antibacterial activity and can effectively inhibit the growth and reproduction of bacteria; these components play a synergistic effect in the antibacterial process, significantly improving the antibacterial effect. DETAILED DESCRIPTION

[0039] The present application will be further described below in conjunction with examples, but the present application is not limited to these examples.

[0040] Example 1 Preparation of modified flame retardant:

[0041] S1: 1000 ml of anhydrous ethanol, 1.2 mol of triethylene glycol monoethyl ether, 1.2 mol of sodium hydroxide were sequentially added into a reactor, stirred and mixed, warmed to 40°C, 1 mol of 2-chloro-4-aminophenol was added in batches (0.2 mol per batch, interval 5 min), reacted for 10 h, then cooled to room temperature, stirred to precipitate crystals, centrifuged and filtered, washed with dichloromethane 3 times (200 ml of dichloromethane was used each time), distilled at 50°C under reduced pressure for 3 h to obtain a polyether compound; the reaction equation is as follows:

[0042]

[0043] S2: 3000 ml of chloroform, 2 mol of polyformaldehyde, 1 mol of polyether compound, 2 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added into a reactor, stirred and mixed, warmed to reflux for 12 h, cooled to room temperature, stirred to precipitate crystals, filtered, then washed with anhydrous ethanol 3 times (500 ml of anhydrous ethanol was used each time), vacuum dried at 50°C for 3 h to obtain a flame retardant compound; the reaction equation is as follows:

[0044]

[0045] The nuclear magnetic resonance hydrogen spectrum data are as follows: 1 H NMR (500 MHz, Chloroform-d) δ 8.25 (dd, J =7.4, 1.2 Hz, 2H), 8.11 (dd, J = 7.1, 1.4 Hz, 2H), 7.95 – 7.88 (m, 2H), 7.77(td, J = 7.1, 1.2 Hz, 2H), 7.60 (td, J = 7.3, 1.4 Hz, 2H), 7.48 – 7.40 (m,6H), 6.77 (d, J = 9.2 Hz, 1H), 6.64 (dd, J = 9.2, 2.2 Hz, 1H), 6.50 (d, J =2.2 Hz, 1H), 6.42 (s, 1H), 4.26 (s, 4H), 4.19 (t, J = 5.0 Hz, 2H), 3.79 (t, J= 5.0 Hz, 2H), 3.72 – 3.51 (m, 10H), 1.21 (t, J = 6.2 Hz, 3H).

[0046] S3: Under nitrogen protection, 1000 ml of tetrahydrofuran, 0.6 mol of the flame retardant compound, 17 g of potassium carbonate were added into a reactor, stirred and mixed uniformly, and then a tetrahydrofuran solution of hexachlorocyclotriphosphazene (0.1 mol of hexachlorocyclotriphosphazene was dissolved in 500 ml of tetrahydrofuran) was slowly added dropwise, the dropping was completed in 1 h, the temperature was raised to reflux, and after 40 h of reaction, the temperature was lowered to 0°C, the crystals were stirred and precipitated, filtered, then washed with 500 ml of deionized water, finally recrystallized by adding 500 ml of ethyl acetate, and vacuum dried at 50°C for 4 h to obtain the modified flame retardant.

[0047] Example 2 Preparation of a modified flame retardant:

[0048] S1: 1000 ml of anhydrous ethanol, 1.3 mol of triethylene glycol monoethyl ether, and 1.2 mol of sodium hydroxide were sequentially added into a reactor, stirred and mixed uniformly, the temperature was raised to 50°C, and 1 mol of 2-chloro-4-aminophenol was added in batches (0.2 mol per batch, with an interval of 5 min between batches), after 9 h of reaction, the temperature was lowered to room temperature, the crystals were stirred and precipitated, centrifuged and filtered, washed with dichloromethane for 3 times (200 ml of dichloromethane was used each time), and vacuum distilled at 60°C for 2 h to obtain the polyether compound;

[0049] S2: 3000 ml of chloroform, 2.5 mol of paraformaldehyde, 1 mol of the polyether compound, and 2.3 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added into a reactor, stirred and mixed uniformly, the temperature was raised to reflux, and after 14 h of reaction, the temperature was lowered to room temperature, the crystals were stirred and precipitated, filtered, then washed with anhydrous ethanol for 3 times (500 ml of anhydrous ethanol was used each time), and vacuum dried at 60°C for 2 h to obtain the flame retardant compound;

[0050] S3: Under nitrogen protection, 1000 ml of tetrahydrofuran, 0.7 mol of the flame retardant compound, and 17 g of potassium carbonate were added into a reactor, stirred and mixed uniformly, and then a tetrahydrofuran solution of hexachlorocyclotriphosphazene (0.1 mol of hexachlorocyclotriphosphazene was dissolved in 500 ml of tetrahydrofuran) was slowly added dropwise, the dropping was completed in 1 h, the temperature was raised to reflux, and after 45 h of reaction, the temperature was lowered to 0°C, the crystals were stirred and precipitated, filtered, then washed with 500 ml of deionized water, finally recrystallized by adding 500 ml of ethyl acetate, and vacuum dried at 60°C for 3 h to obtain the modified flame retardant.

[0051] Example 3 Preparation of a modified flame retardant:

[0052] S1: 1000 ml of anhydrous ethanol, 1.5 mol of triethylene glycol monoethyl ether, 1.2 mol of sodium hydroxide were sequentially added to the reactor, stirred and mixed, warmed to 60°C, and 1 mol of 2-chloro-4-aminophenol was added in batches (0.2 mol per batch, interval 5 min), reacted for 8 h, then cooled to room temperature, stirred to precipitate crystals, centrifuged and filtered, washed with dichloromethane 3 times (400 ml of dichloromethane was used each time), distilled at 70°C under reduced pressure for 1 h, and a polyether bond compound was obtained;

[0053] S2: 3000 ml of chloroform, 3 mol of paraformaldehyde, 1 mol of the polyether bond compound, and 2.5 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to the reactor, stirred and mixed, warmed to reflux for 16 h, cooled to room temperature, stirred to precipitate crystals, filtered, then washed with anhydrous ethanol 3 times (500 ml of anhydrous ethanol was used each time), and a flame retardant compound was obtained by vacuum drying at 70°C for 1 h;

[0054] S3: Under nitrogen protection, 1000 ml of tetrahydrofuran, 0.8 mol of the flame retardant compound, and 17 g of potassium carbonate were added to the reactor, stirred and mixed, then a tetrahydrofuran solution of hexachlorocyclotriphosphazene (0.1 mol of hexachlorocyclotriphosphazene was dissolved in 500 ml of tetrahydrofuran) was slowly added dropwise, the dropwise addition was performed for 1 h, the temperature was warmed to reflux, the reaction was performed for 48 h, then cooled to 0°C, stirred to precipitate crystals, filtered, then washed with 500 ml of deionized water, finally recrystallized by adding 500 ml of ethyl acetate, and the modified flame retardant was obtained by vacuum drying at 70°C for 2 h.

[0055] Example 4: Preparation of a modified antibacterial agent:

[0056] S1: Under nitrogen protection, 1000 g of DMSO, 250 g of 3-(bis(2-hydroxyethyl)amino)propionic acid methyl ester, and 50 g of 1,2-propanediol were added to the reactor, stirred and mixed, warmed to 75°C, then 8 g of p-toluenesulfonic acid was added, the reaction was performed for 6 h, then cooled to room temperature, a saturated sodium bicarbonate solution was slowly added to adjust the pH to neutral, stirred for 30 min, allowed to stand and separate into layers, the organic phase was transferred to a rotary evaporator, distilled under reduced pressure at 65°C for 3 h, and the hyperbranched product was obtained by vacuum drying at 70°C for 2 h;

[0057] S2: Under nitrogen protection, 800 ml of toluene, 60 g of 3-mercaptopropionic acid, and 100 g of the hyperbranched product were added to the reactor, stirred and mixed, warmed to 80°C, then 10 g of p-toluenesulfonic acid was added, the reaction was performed for 5 h (a water trap was used to remove the generated water during the reaction), then cooled to room temperature, a saturated sodium bicarbonate solution was slowly added to adjust the pH to neutral, stirred for 30 min, allowed to stand and separate into layers, the organic phase was transferred to a rotary evaporator, distilled under reduced pressure at 70°C for 2 h, and the mercapto hyperbranched product was obtained by vacuum drying at 60°C for 4 h;

[0058] S3: 1000 ml of DMSO, 180 g of the mercapto-hyperbranched product and 60 g of 3-mercaptopropionic acid were added to a reactor, stirred and mixed, warmed to 80°C, reacted for 12 h, then extracted three times with 600 ml of saturated sodium chloride solution, distilled at reduced pressure for 3 h at 60°C, and then separated using a silica gel column to obtain the dithio-hyperbranched product;

[0059] S4: 1000 ml of anhydrous dichloromethane, 150 g of the dithio-hyperbranched product and 40 g of silver sulfadiazine were added to a reactor under nitrogen protection, stirred and mixed, 20 g of N,N'-dicyclohexyl carbodiimide was added in batches (5 g each, with a 5 min interval between batches), then 1.5 g of 4-dimethylaminopyridine was added, reacted for 12 h at room temperature, filtered, washed with 500 ml of saturated sodium bicarbonate solution, 500 ml of deionized water in sequence, dried with 100 g of anhydrous sodium sulfate for 30 min, rotary evaporated at 40°C for 2 h, and vacuum dried at 40°C for 5 h to obtain the modified antibacterial agent.

[0060] Example 5: Preparation of a modified antibacterial agent

[0061] S1: 1000 g of DMSO, 280 g of methyl 3-(bis(2-hydroxyethyl)amino)propionate and 50 g of 1,2-propanediol were added to a reactor under nitrogen protection, stirred and mixed, warmed to 80°C, then 8 g of p-toluenesulfonic acid was added, reacted for 5 h, then cooled to room temperature, a saturated sodium bicarbonate solution was slowly added to adjust the pH to neutral, stirred thoroughly for 30 min, and then allowed to separate into layers. The organic phase was transferred to a rotary evaporator, distilled at reduced pressure for 3 h at 65°C, and vacuum dried at 70°C for 2 h to obtain the hyperbranched product;

[0062] S2: 800 ml of toluene, 60 g of 3-mercaptopropionic acid and 120 g of the hyperbranched product were added to a reactor under nitrogen protection, stirred and mixed, warmed to 90°C, then 10 g of p-toluenesulfonic acid was added, reacted for 4 h (a water separator was used to remove the generated water during the reaction), then cooled to room temperature, a saturated sodium bicarbonate solution was slowly added to adjust the pH to neutral, stirred thoroughly for 30 min, and then allowed to separate into layers. The organic phase was transferred to a rotary evaporator, distilled at reduced pressure for 3 h at 60°C, and vacuum dried at 70°C for 3 h to obtain the mercapto-hyperbranched product;

[0063] S3: 1000 ml of DMSO, 190 g of the mercapto-hyperbranched product and 60 g of 3-mercaptopropionic acid were added to a reactor, stirred and mixed, warmed to 90°C, reacted for 10 h, then extracted three times with 600 ml of saturated sodium chloride solution, distilled at reduced pressure for 4 h at 60°C, and then separated using a silica gel column to obtain the dithio-hyperbranched product;

[0064] S4: Under nitrogen protection, 1000 ml of anhydrous dichloromethane, 180 g of the dithio hyperbranched product and 40 g of sulfadiazine silver were added to the reactor, stirred and mixed, 25 g of N,N'-dicyclohexyl carbodiimide was added at 10 °C (5 g each time, interval 5 min), then 1.5 g of 4-dimethylamino pyridine was added, and the reaction was carried out at room temperature for 10 h, filtered, washed with 500 ml of saturated sodium bicarbonate solution, 500 ml of deionized water, dried with 100 g of anhydrous sodium sulfate for 30 min, rotary evaporated at 40 °C for 2 h, and vacuum dried at 40 °C for 5 h to obtain the modified antibacterial agent.

[0065] Example 6: Preparation of modified antibacterial agent

[0066] S1: Under nitrogen protection, 1000 g of DMSO, 300 g of 3-(bis(2-hydroxyethyl)amino) methyl propionate, and 50 g of 1,2-propanediol were added to the reactor, stirred and mixed, heated to 90 °C, then 8 g of p-toluenesulfonic acid was added, the reaction was carried out for 4 h, then cooled to room temperature, the pH was adjusted to neutral by slowly adding saturated sodium bicarbonate solution, stirred for 30 min, and then the organic phase was transferred to a rotary evaporator and distilled at 65 °C under reduced pressure for 3 h, and then vacuum dried at 70 °C for 2 h to obtain the hyperbranched product;

[0067] S2: Under nitrogen protection, 800 ml of toluene, 60 g of 3-mercapto propionic acid, and 150 g of the hyperbranched product were added to the reactor, stirred and mixed, heated to 100 °C, then 10 g of p-toluenesulfonic acid was added, the reaction was carried out for 3 h (water generated during the reaction was removed using a water trap), then cooled to room temperature, the pH was adjusted to neutral by slowly adding saturated sodium bicarbonate solution, stirred for 30 min, and then the organic phase was transferred to a rotary evaporator and distilled at 60 °C under reduced pressure for 3 h, and then vacuum dried at 50 °C for 5 h to obtain the mercapto hyperbranched product;

[0068] S3: 1000 ml of DMSO, 200 g of the mercapto hyperbranched product and 60 g of 3-mercapto propionic acid were added to the reactor, stirred and mixed, heated to 100 °C, and the reaction was carried out for 8 h, then extracted with 600 ml of saturated sodium chloride solution three times, distilled at 70 °C under reduced pressure for 2 h, and then separated using a silica gel column to obtain the dithio hyperbranched product;

[0069] S4: Under nitrogen protection, 1000 ml of anhydrous dichloromethane, 200 g of the dithio hyperbranched product and 40 g of sulfadiazine silver were added into a reactor, stirred and mixed uniformly, 30 g of N,N'-dicyclohexyl carbodiimide was added in batches (5 g each time, interval 5 min), then 1.5 g of 4-dimethylaminopyridine was added, reacted at room temperature for 8 h, filtered, washed with 500 ml of saturated sodium bicarbonate solution, 500 ml of deionized water, dried with 100 g of anhydrous sodium sulfate for 30 min, rotary evaporated at 40℃ for 2 h, and vacuum dried at 40℃ for 5 h to obtain the modified antibacterial agent.

[0070] Example 7: Preparation of a wear-resistant nitrile composite material:

[0071] (1) Take: nitrile rubber 1000 g, nano-silicon dioxide 150 g, plasticizer (dioctyl phthalate) 80 g, zinc oxide 30 g, stearic acid 10 g, antioxidant (antioxidant 1010) 20 g, modified flame retardant (prepared in example 1) 30 g, modified antibacterial agent (prepared in example 4) 50 g, coupling agent (γ-aminopropyl triethoxysilane) 10 g;

[0072] (2) Mix the nano-silicon dioxide and the coupling agent in proportion, place them in a high-speed stirrer and stir uniformly for 10 min to obtain surface-modified nano-silicon dioxide; mix the nitrile rubber, zinc oxide and stearic acid, and pass them through a banbury mixer at 120℃ for 10 min to prepare a masterbatch;

[0073] (3) Add the masterbatch, surface-modified nano-silicon dioxide, plasticizer, antioxidant, modified flame retardant and modified antibacterial agent into a twin-screw extruder, set the temperature to 160℃ and the screw speed to 300 r / min, melt blend and then extrude and granulate; press the extruded and granulated composite material particles to obtain a wear-resistant nitrile composite material.

[0074] Example 8: Preparation of a wear-resistant nitrile composite material:

[0075] (1) Take: nitrile rubber 1000 g, nano-silicon dioxide 200 g, plasticizer (diisononyl phthalate) 100 g, zinc oxide 40 g, stearic acid 20 g, antioxidant (antioxidant 1076) 25 g, modified flame retardant (prepared in example 2) 40 g, modified antibacterial agent (prepared in example 5) 60 g, coupling agent (vinyl triethoxysilane) 20 g;

[0076] (2) Mix the nano-silicon dioxide and the coupling agent in proportion, place them in a high-speed stirrer and stir uniformly for 15 min to obtain surface-modified nano-silicon dioxide; mix the nitrile rubber, zinc oxide and stearic acid, and pass them through a banbury mixer at 130℃ for 8 min to prepare a masterbatch;

[0077] (3) The masterbatch, surface-modified nano-silica and plasticizer, antioxidant, modified flame retardant, modified antibacterial agent are added into the twin-screw extruder, the temperature is set to 170°C, the screw speed is 350 r / min, and after melt blending, the extrusion granulation is carried out; the composite material particles after extrusion granulation are pressed into shape to obtain the wear-resistant nitrile composite material.

[0078] Example 9 Preparation of a wear-resistant nitrile composite material:

[0079] (1) 1000 g of nitrile rubber, 250 g of nano-silica, 120 g of plasticizer (dibutyl phthalate), 50 g of zinc oxide, 30 g of stearic acid, 30 g of antioxidant (antioxidant 168), 50 g of modified flame retardant (prepared in Example 3), 80 g of modified antibacterial agent (prepared in Example 6), and 30 g of coupling agent (γ-methacryloyloxypropyltrimethoxysilane);

[0080] (2) The nano-silica and the coupling agent are mixed in proportion, stirred uniformly in a high-speed stirrer, and the treatment time is 20 min to obtain surface-modified nano-silica; the nitrile rubber, zinc oxide and stearic acid are mixed and kneaded by a banbury mixer at 150°C for 5 min to prepare a masterbatch;

[0081] (3) The masterbatch, surface-modified nano-silica and plasticizer, antioxidant, modified flame retardant, modified antibacterial agent are added into the twin-screw extruder, the temperature is set to 180°C, the screw speed is 400 r / min, and after melt blending, the extrusion granulation is carried out; the composite material particles after extrusion granulation are pressed into shape to obtain the wear-resistant nitrile composite material.

[0082] Comparative Example 1

[0083] The raw material composition and process of the wear-resistant nitrile composite material are basically the same as those of Example 8, except that the modified flame retardant is replaced by an equal weight of modified flame retardant prepared by the following method:

[0084] The preparation method of the modified flame retardant is basically the same as that of Example 2, except that the triethylene glycol monoethyl ether in step S1 is replaced by an equal weight of n-propanol.

[0085] Comparative Example 2

[0086] The raw material composition and process of the wear-resistant nitrile composite material are basically the same as those of Example 8, except that the modified flame retardant is replaced by an equal weight of modified flame retardant prepared by the following method:

[0087] The preparation method of the modified flame retardant is basically the same as that of Example 2, except that the hexachlorotriphosphazene in step S3 is replaced by an equal weight of phenylphosphonic dichloride.

[0088] Comparative Example 3

[0089] The raw material composition and process of the wear-resistant nitrile composite were basically the same as those of Example 8, except that the modified flame retardant was replaced with an equal weight of a modified flame retardant prepared by the following method:

[0090] The preparation method of the modified flame retardant was basically the same as that of Example 2, except that 2-chloro-4-aminophenol in step S1 was replaced with an equal weight of 4-chloro-2-[(methylamino)methyl]phenol.

[0091] Comparative Example 4

[0092] The raw material composition and process of the wear-resistant nitrile composite were basically the same as those of Example 8, except that the modified antibacterial agent was replaced with an equal weight of a modified antibacterial agent prepared by the following method:

[0093] The preparation method of the modified antibacterial agent was basically the same as that of Example 5, except that 1,2-propanediol in step S1 was replaced with an equal weight of pentaerythritol.

[0094] Comparative Example 5

[0095] The raw material composition and process of the wear-resistant nitrile composite were basically the same as those of Example 8, except that the modified antibacterial agent was replaced with an equal weight of a modified antibacterial agent prepared by the following method:

[0096] The preparation method of the modified antibacterial agent was basically the same as that of Example 5, except that 3-(bis(2-hydroxyethyl)amino)propionic acid methyl ester in step S1 was replaced with an equal weight of 3-[(2-hydroxyethyl)amino]propionic acid methyl ester.

[0097] Comparative Example 6

[0098] The raw material composition and process of the wear-resistant nitrile composite were basically the same as those of Example 8, except that the modified antibacterial agent was replaced with an equal weight of a modified antibacterial agent prepared by the following method:

[0099] The preparation method of the modified antibacterial agent was basically the same as that of Example 5, except that 3-mercaptopropionic acid in step S2 was replaced with an equal weight of malic acid.

[0100] Comparative Example 7

[0101] The raw material composition and process of the wear-resistant nitrile composite were basically the same as those of Example 8, except that the modified antibacterial agent was replaced with an equal weight of a modified antibacterial agent prepared by the following method:

[0102] The preparation method of the modified antibacterial agent was basically the same as that of Example 5, except that silver sulfadiazine in step S4 was replaced with an equal weight of sulfadiazine.

[0103] Comparative Example 8

[0104] A high-temperature-resistant nitrile rubber composite material was prepared by using the raw material composition and the preparation process of Example 4 of the Chinese patent application with the publication number CN103012881A.

[0105] The nitrile rubber used in the examples and comparative examples of the present application was DN3350, purchased from Japan Zeon Corporation; the nano-silica particle size was 15 nm, purchased from Shanghai Silp Chemical Co., Ltd.; the paraformaldehyde was PF-03, purchased from Nantong Jiangshan Pesticide Chemical Co., Ltd.

[0106] The wear-resistant nitrile composite materials prepared in Examples 7-9 and Comparative Examples 1-10 of the present application were subjected to performance tests, and the test results are shown in Table 1.

[0107] The abrasion test was tested according to GB / T 9867-2008; the antibacterial test was tested according to GB / T 31402-2015; the flame retardant test was tested according to GB / T 10707-2008, and the test results are shown in Table 1.

[0108] Table 1 Performance test table

[0109]

[0110] As can be seen from Table 1, the wear-resistant nitrile composite materials prepared in Examples 7-9 of the present application have excellent wear resistance, flame retardancy and antibacterial properties.

[0111] Comparative Example 1 is different from Example 8, the difference is that the triethylene glycol monoethyl ether in step S1 in the preparation process of the modified flame retardant is replaced by n-propanol, and its wear resistance performance is poor. The present application introduces triethylene glycol monoethyl ether into the flame retardant, so that the synthesized modified flame retardant contains multiple ether bonds, which enhances the compatibility between the nitrile material and the flame retardant, so that the components of the nitrile material can be more evenly distributed, thereby improving the mechanical properties of the material.

[0112] The modified flame retardant prepared in the present application introduces phosphorus elements by introducing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and hexachlorocyclotriphosphazene introduces nitrogen elements; phosphorus and nitrogen have a synergistic effect in the flame retardant process, phosphorus can promote the formation of a stable carbon layer on the surface of the material during combustion, thereby playing a role in isolating oxygen and combustible gases; nitrogen can release non-combustible gases during combustion, dilute the concentration of oxygen and combustible gases, and reduce the combustion rate; at the same time, hexachlorocyclotriphosphazene has multiple reactive sites, which can form a three-dimensional network structure when reacting with the flame-retardant compound to form a modified flame retardant. This network structure can improve the thermal stability and mechanical properties of the material, making it more difficult to decompose and burn at high temperatures, thereby enhancing the flame retardant effect. However, benzophosphoryl dichloride cannot form a network structure.

[0113] In Comparative Example 3, 2-chloro-4-aminophenol in step S1 of the preparation process of the modified flame retardant is replaced with an equal weight of 4-chloro-2-[(methylamino)methyl]phenol, which may be due to the fact that 4-chloro-2-[(methylamino)methyl]phenol can only react with one molecule of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, resulting in fewer phosphorus-containing functional groups being introduced into the prepared flame retardant.

[0114] The modified antibacterial agent prepared in the present application has a hyperbranched structure, providing more active sites and a larger specific surface area, enhancing the interaction between the antibacterial agent and the bacterial cell membrane; the dithio structure can react with bacterial proteins and enzymes, destroying the cell structure of the bacteria; sulfadiazine silver has broad-spectrum antibacterial activity and can effectively inhibit the growth and reproduction of bacteria; the sulfonic acid group in sulfadiazine silver has strong negative charge and can bind to the positively charged bacterial membrane through electrostatic interaction, destroying the membrane structure stability; the Ag + released by sulfadiazine silver binds to the membrane protein of the bacteria, causing membrane perforation; at the same time, Ag + enters the cell and binds to DNA / RNA, inhibiting replication. The negative charge of the sulfonic acid group can adsorb positively charged Ag + , delaying its release rate and avoiding the rapid inactivation of Ag + , thus having long-acting antibacterial properties.

[0115] Comparative Example 4 uses pentaerythritol to prepare hyperbranched antibacterial agent, the density between functional groups in the hyperbranched product is higher, which leads to lower mixing homogeneity in the nitrile composite. However, Comparative Example 5 uses 3-[(2-hydroxyethyl)amino] propionic acid methyl ester which only contains one hydroxyl group, the density of the hyperbranched product is too sparse, and the generated disulfide bond is less, the antibacterial performance is reduced. Comparative Example 6 uses malic acid instead of 3-mercaptopropionic acid, and then the disulfide bond cannot be formed. Comparative Example 7 uses sulfadiazine instead of silver sulfadiazine, and there is no silver ion synergy.

[0116] Comparative Example 8 is a high-temperature-resistant nitrile rubber composite material prepared by using the raw material composition and manufacturing process of Example 4 of the Chinese invention patent with publication number CN103012881A. As can be seen from the data in Table 1, its flame retardance and wear resistance are not as good as the present application.

[0117] The above description is only the preferred embodiments of the present application and is not intended to limit the present application; but for the ordinary skilled in the art without departing from the scope of the technical solutions of the present application, some minor changes, modifications and equivalent changes of the above disclosed technical content can be made, which are equivalent embodiments of the present application; at the same time, any equivalent changes, modifications and evolution of the above embodiments according to the essential technology of the present application are still within the protection scope of the technical solutions of the present application.

Claims

1. A wear-resistant nitrile butadiene composite material, characterized in that, The ingredients include the following parts by weight: 100 parts nitrile rubber, 15-25 parts nano silica, 8-12 parts plasticizer, 3-5 parts zinc oxide, 1-3 parts stearic acid, 2-3 parts antioxidant, 3-5 parts modified flame retardant, 5-8 parts modified antibacterial agent, and 1-3 parts coupling agent. The modified flame retardant is prepared by the following method: S1: 2-Chloro-4-aminophenol reacts with triethylene glycol monoethyl ether in the presence of sodium hydroxide to form a polyether compound; S2: Polyether compounds, paraformaldehyde, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide react to form flame-retardant compounds; S3: Nitrogen protection, hexachlorocyclotriphosphazene reacts with flame retardant compounds in the presence of potassium carbonate to generate a modified flame retardant; The modified antibacterial agent is prepared by the following method: A1: Under nitrogen protection, methyl 3-(bis(2-hydroxyethyl)amino)propionate reacts with 1,2-propanediol in p-toluenesulfonic acid to form a hyperbranched product; A2: Under nitrogen protection, 3-mercaptopropionic acid reacts with hyperbranched products in the presence of p-toluenesulfonic acid to generate thiol hyperbranched products; A3: The thiol hyperbranched product reacts with 3-mercaptopropionic acid to generate a dithiohyperbranched product; A4: Under nitrogen protection, the dithiohyperbranched product reacts with silver sulfadiazine under the catalysis of N,N'-dicyclohexylcarbodiimide to generate a modified antibacterial agent.

2. The wear-resistant nitrile composite material according to claim 1, characterized in that, In step S1, the molar ratio of 2-chloro-4-aminophenol to triethylene glycol monoethyl ether is 1:(1.2-1.5).

3. The wear-resistant nitrile composite material according to claim 1, characterized in that, In step S2, the molar ratio of the paraformaldehyde, the polyether compound, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is (2-3):1:(2-2.5).

4. The wear-resistant nitrile butadiene composite material according to claim 1, characterized in that, In step S3, the molar ratio of the hexachlorocyclotriphosphazene and the flame retardant compound is 1:(6-8).

5. The wear-resistant nitrile composite material according to claim 1, characterized in that, In step A1, the mass ratio of methyl 3-(bis(2-hydroxyethyl)amino)propionate to 1,2-propanediol is (25-30):

5.

6. The wear-resistant nitrile composite material according to claim 1, characterized in that, In step A2, the mass ratio of 3-mercaptopropionic acid to hyperbranched product is 6:(10-15).

7. The wear-resistant nitrile composite material according to claim 1, characterized in that, In step A3, the mass ratio of the thiol hyperbranched product to 3-mercaptopropionic acid is (18-20):

6.

8. The wear-resistant nitrile composite material according to claim 1, characterized in that, In step A4, the mass ratio of the dithiohyperbranched product to silver sulfadiazine is (15-20):

4.

9. The wear-resistant nitrile butadiene composite material according to claim 1, characterized in that, The plasticizer is one of dioctyl phthalate, diisononyl phthalate, and dibutyl phthalate.

10. The wear-resistant nitrile composite material according to claim 1, characterized in that, The antioxidant is one of antioxidant 1010, antioxidant 1076, and antioxidant 168.

11. The wear-resistant nitrile composite material according to claim 1, characterized in that, The coupling agent is one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.

12. A method for preparing the wear-resistant nitrile butadiene composite material according to any one of claims 1-11, characterized in that, Includes the following steps: (1) Weigh out the following by weight: 100 parts of nitrile rubber, 15-25 parts of nano silica, 8-12 parts of plasticizer, 3-5 parts of zinc oxide, 1-3 parts of stearic acid, 2-3 parts of antioxidant, 3-5 parts of modified flame retardant, 5-8 parts of modified antibacterial agent, and 1-3 parts of coupling agent. (2) Mix nano-silica with coupling agent in proportion, place in a high-speed mixer and stir evenly for 10-20 min to obtain surface-modified nano-silica; mix nitrile rubber, zinc oxide and stearic acid, and knead in an internal mixer at 120-150℃ for 5-10 min to make masterbatch; (3) Add the masterbatch, surface-modified nano silica, plasticizer, antioxidant, modified flame retardant and modified antibacterial agent into a twin-screw extruder, set the temperature to 160-180℃ and the screw speed to 300-400r / min, melt blend and then extrude granulate; press the extruded granulated composite material particles into shape to obtain wear-resistant nitrile composite material.

13. The application of a wear-resistant nitrile composite material as described in any one of claims 1-11 in the field of additive manufacturing.

Citation Information

Patent Citations

  • Heat-resistant nitrile rubber composite material

    CN103012881A

  • Fire-extinguishing composition containing amino acid compounds

    CN103170082A

  • Antibacterial PP material and preparation method thereof

    CN119264554A